Dynamic collapse analysis for a reinforced concrete frame sustaining shear and axial failures. - Elwood, Kenneth J.
Shaking table test results from a one-story, two-bay reinforced concrete frame sustaining shear and axial failures are compared with nonlinear dynamic analyses using models developed for the collapse assessment of older reinforced concrete buildings. The models provided reasonable estimates of the overall frame response and lateral strength degradation; however, the measured drifts were underestimated by the models. Selected model parameters were varied to investigate the sensitivity of the calculated response to changes in the drift at shear failure, rate of shear strength degradation, and drift at axial failure. For the selected ground motion, the drift at shear failure and rate of shear strength degradation did not have a significant impact on the calculated peak drift. By incorporating shear and axial-load failure models, the analytical model is shown to be capable of predicting the axial-load failure for a hypothetical frame with three nonductile columns. Improvements are needed in drift demand estimates from nonlinear dynamic analysis if such analyses are to be used in displacement-based performance assessments.
Keywords: Nonlinear dynamic analysis; Shear failure; Axial-load failure; Reinforced concrete columns; Collapse; Shaking table test